CHALLENGES TO PHYSICAL EDUCATION IN MEXICO (Fiep Bulletin - online, 2012)
This work was developed from the analysis of some authors interested in the trends of Physical Education and Sports. It features an overview of physical practices, relating them to socio-cultural contributions and influence of historical and political facts in the formation and development of Physical Education in Mexico. As of 1923 several actions favored the development of Physical Education in Mexico, such as the creation of the Mexican Olympic Committee (Comité Olímpico Mexicano), the creation of the National Physical Education School (Escuela Nacional de Educación Física) in 1932, among other relevant facts. The accomplishment of the Olympic Games in Mexico in 1968, followed by other international events, was a landmark in the development of Physical Education and Sports in the country. On the other hand, Mexican professionals started being indicated to occupy positions in Physical Education international organizations. The evolution of Physical Education programs is included in this paper. Originally these programs were sports-oriented; later they adopted a psychomotor guideline, and now they have a functional-organic focus.This paper also approaches globalization in education with its positive and negative influences on Physical Education. It features the Physical Education trends pointed out by Dr. Manoel Tubino in several conferences and proposes a series of questions related to School Physical Education. Finally, it presents a list of challenging actions that must be implemented for the sake of Physical Education development in Mexico.
Keywords: Physical Education; globalization; trends; challenges.